Uji Stabilitas Obat Sediaan Tablet: Prinsip, Pedoman ICH Q1, dan Parameter Kritis - Jannatun Nisa; Nicky Saputra; Nor Latifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This article provides a comprehensive review of drug stability testing, specifically focusing on tablet dosage forms. It elucidates the fundamental principles, the critical role of ICH Q1 guidelines, and essential parameters evaluated during stability studies, including physical, chemical, and microbiological aspects. The discussion covers various types of stability studies, standardized storage conditions, and the interpretation of results for determining shelf life and ensuring product quality. Relevant case studies on tablet stability are also integrated to illustrate practical applications. This review aims to provide a structured overview of stability testing methodologies and their significance in pharmaceutical development and quality assurance.